A novel computer-assisted workflow for treatment of osteochondral lesions in the knee - Tatti,F; Iqbal,H; Jaramaz,B; Rodriguez,Y Baena F (EasyChair, 2020)
Computer-Assisted Orthopaedic Surgery (CAOS) is now becoming more prevalent, especially in knee arthroplasty. CAOS systems have the potential to improve the accuracy and repeatability of surgical procedures by means of digital preoperative planning and intraoperative tracking of the patient and surgical instruments.One area where the accuracy and repeatability of computer-assisted interventions could prove especially beneficial is the treatment of osteochondral defects (OCD). OCDs represent a common problem in the patient population, and are often a cause of pain and discomfort. The use of synthetic implants is a valid option for patients who cannot be treated with regenerative methods, but the outcome can be negatively impacted by incorrect positioning of the implant and lack of congruency with the surrounding anatomy.In this paper, we present a novel computer-assisted surgical workflow for the treatment of osteochondral defects. The software we developed automatically selects the implant that most closely matches the patient’s anatomy and computes the best pose. By combining this software with the existing capabilities of the Navio™ surgical system (Smith & Nephew inc.), we were able to create a complete workflow that incorporates both surgical planning and assisted bone preparation.Our preliminary testing on plastic bone models was successful and demonstrated that the workflow can be used to select and position an appropriate implant for a given defect.